2000
DOI: 10.1002/1522-2632(200011)85:5/6<561::aid-iroh561>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Spreading and Establishment of the Potentially Toxic Dinoflagellate Prorocentrum minimum in the Baltic Sea

Abstract: During the last two decades the potentially toxic dinoflagellate Prorocentrum minimum (PAVILLARD) SCHILLER has successfully established itself in the Baltic Sea. It is now a dominant summer species in the southern Baltic proper, and reaches as far into the low salinity of the northern Baltic as the central Gulf of Finland. In the 1990s, it developed several coastal blooms in the eastern and northern Baltic proper, but occurred irregularly between years. Field data show that P. minimum can grow at salinities be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 11 publications
3
54
1
Order By: Relevance
“…Different shaped P. minimum cells were often present in the same samples in both studies. Generalizations made concerning relationships between P. minimum morphology and geographical distributions and salinity must be regarded with caution, however, as Pertola et al (2003Pertola et al ( , 2005 reported relationships between cell shape that are contrary to those reported by Hajdu et al (2000).…”
Section: Taxonomy and Systematicsmentioning
confidence: 83%
See 2 more Smart Citations
“…Different shaped P. minimum cells were often present in the same samples in both studies. Generalizations made concerning relationships between P. minimum morphology and geographical distributions and salinity must be regarded with caution, however, as Pertola et al (2003Pertola et al ( , 2005 reported relationships between cell shape that are contrary to those reported by Hajdu et al (2000).…”
Section: Taxonomy and Systematicsmentioning
confidence: 83%
“…This variability in cell shape has often led to the description of local forms as new species Marasović et al, 1990), leading to the variety of synonyms for P. minimum in the literature ( Table 1). Examples of the morphological variability of this species are given by Hulburt (1965), who examined clones isolated from blooms around Woods Hole, Massachusetts and Long Island, New York, and Hajdu et al (2000) who examined variability in P. minimum cell size in different areas of the Baltic Sea. Hulburt (1965) reported a gradation in P. minimum shape from triangular to heart-shaped and oval, with a considerable overlap in size.…”
Section: Taxonomy and Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Danilov & Ekelund (2001) showed that several biodiversity indices failed in coastal monitoring of Baltic Sea areas. Moreover, Wasmund et al (2000) discussed that potential taxonomic group indicators like (Dino-) flagellates or Diatom biomass described in Radach et al (1990), Conley et al (1993) and Hajdu et al (2000) were also not applicable. The lack of useful taxonomy-based evaluation systems for Baltic brackish coastal areas is probably caused by the high temporal and spatial variability of hydrological and geochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hajdu et al (2000) demonstrated that cultures of P. minimum adapted to each salinity treatment showed higher growth than those directly inoculated into each experimental treatment. However, the optimum salinity conditions did not change due to the adaptation in the experiment.…”
mentioning
confidence: 99%